Executive Performance Is Associated With Rest-Activity Rhythm in Nurses Working Rotating Shifts - Zhao, Xiuli; Tang, Quan; Feng, Zhengzhi; Zhào, Hóngyi (Frontiers in Neuroscience, 2022)
Purpose: Rest-activity rhythms (RAR) is one of the most fundamental biological patterns that influence basic physical and mental health, as well as working performance. Nowadays, with the utilization of actigraphy device in detecting and analyzing RAR objectively, evidence has confirmed that RAR could be interrupted by shift work. Nurses need to participate shift work in their daily routine. The aim of the present study is to identify the RAR of nurses working rotating shifts and find out the relationship between RAR and executive function. Methods: A total of 11 female nurses on day-shift (DS), 11 female nurses on rotating-shift (RS) were recruited. Demographic features, nonparametric variables of RAR as well as sleep variables according to actigraphy data, and a series of cognitive function evaluations during work time were collected. Results: The Student’s t-test comparison revealed that RS group nurses showed significant shorter total sleep time (TST), lower level of interdaily stability (IS) and relative amplitude (RA), as well as poorer executive performance compared with DS nurses. Bivariate correlation exhibited that relative amplitude (RA), instead of IS and IV, correlated with sleep variables. The linear regression analysis demonstrated that executive performance such choice reaction test (CRT) (reflecting attention and concentration), digit symbol substitution test (DSST) (reflecting processing speed) and trail making test (TMT) -B (reflecting cognitive flexibility) was associated with IS in RS group nurses. Conclusion: These results elucidated that RAR was disrupted for nurses working rotating shifts, and executive performance was associated with IS in nurses working rotating shifts.